Prevalence of causative bacteria and clinical outcomes among patients with meningitis at a regional central hospital in Thailand - Santimaleeworagun, Wichai; Jangkong, Nirun; Petchhouyluek, Ketmanee; Leawsrivilai, Nalinrat; Suwanraksa, Wichayaporn; Buapool, Wimonsiri (Science, Engineering and Health Studies, 2019)
This study aimed to identify causative bacteria and to investigate the outcomes of treatment and the appropriate empirical regimen among patients with bacterial meningitis. Patients with bacterial meningitis admitted at Ratchaburi Hospital during January 2012 to December 2016 were included. Of two hundred and eight patients, 76 cases of them with known causative pathogens were included. Fifty-five cases were males (72.4%) and 55.2% of patients were aged 2-50 years. Sixty three out of 76 patients with meningitis (82.9%) were community acquired (CA-) bacterial meningitis. The most frequently found isolated pathogens in 63 CA-bacterial meningitis cases were S. agalactiae followed by S. pneumoniae. While A. baumannii and K. pneumoniae were the top-two isolated organisms among 13 hospital acquired cases. The rates of in-hospital mortality among 76 cases were 18.4%. The third generation cephalosporins plus vancomycin was the most active agent against bacteria (87.3%) isolated from CA-bacterial meningitis whereas carbapenems plus vancomycin remain an effective choice against bacteria (84.6%) isolated from patients with hospital acquired meningitis. However, the most common of causative pathogens were a Gram-positive bacteria in community setting and Gram-negative bacteria in hospital setting. The appropriate empirical regimen against bacteria in both setting have to be further investigated.